Chronological Impact of Earthquakes on Blood Pressure: A Literature Review and Retrospective Study of Hypertension in Haiti Before and After the 2010 Earthquake - Fath, Ayman R.; Aglan, Amro; Platt, Jeri; Yaron, Jordan R.; Varkoly, Kyle S.; Beladi, Roxana N.; Gorgas, Diane; Jean, Jean Tom; Dasni, Pierre; Eldaly, Abdullah S.; Juby, Michael; Lucas, Alexandra R. (Frontiers in Public Health, 2021)
Objective: We review prior studies on the incidence of hypertension (HTN) after earthquakes and present a retrospective analysis of HTN after the 2010 earthquake in Haiti. Methods: Prior reports on HTN incidence were reviewed and a retrospective chart review for diagnosis of HTN in 4,308 patient charts was performed over a 7 year period (5 clinics). A retrospective cohort study (RCS) was then performed on 11 patients with linear follow-up. Results: The literature review revealed a significant increase in acute and subacute HTN following earthquakes. However, the chronic effects of earthquakes varied. Our chart review uncovered no significant difference in diagnosed HTN in a Fort-Liberté clinic 128 kilometers (km) distant and 4 weeks post-event. A secondary linear RCS for 11 individuals, prior to and after the earthquake, also did not detect a significant change in HTN prevalence. Conclusion: Prior studies demonstrate acute and subacute, increases in HTN after earthquakes, but late changes have varied. Retrospective studies in the Fort-Liberté clinic, 128 km distant and 4 weeks post-event, revealed no significant change in HTN, confirming prior findings that changes in HTN after earthquakes are early and local events. Further work examining HTN after earthquakes is needed to improve early health care after natural disasters.